2016
DOI: 10.1186/s12913-016-1511-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to potentially preventable hospitalizations for diabetes and heart failure: a qualitative analysis of patient perspectives

Abstract: BackgroundPotentially preventable hospitalizations (PPH) for heart failure (HF) and diabetes mellitus (DM) cost the United States over $14 billion annually. Studies about PPH typically lack patient perspectives, especially across diverse racial/ethnic groups with known PPH health disparities.MethodsEnglish-speaking individuals with a HF or DM-related PPH (n = 90) at the largest hospital in Hawai‘i completed an in-person interview, including open-ended questions on precipitating factors to their PPH. Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…However, Hawai'i data shows an increase in chronic diseases and obesity over time [20]. The state has notable health disparities; compared to Whites, Native Hawaiians, Filipinos, and other Pacific Islanders are diagnosed with diabetes at earlier ages, have higher rates of hospitalizations for preventable chronic conditions and shorter longevity [19,21,22]. While Hawai'i's official poverty rate is very low, when cost-ofliving is factored in, in 2017 Hawai'i had the 10th highest poverty rate of all states, [23] and rural populations and lower income communities in the state have similar poor outcomes [19,24].…”
Section: Hawai'i Contextmentioning
confidence: 99%
“…However, Hawai'i data shows an increase in chronic diseases and obesity over time [20]. The state has notable health disparities; compared to Whites, Native Hawaiians, Filipinos, and other Pacific Islanders are diagnosed with diabetes at earlier ages, have higher rates of hospitalizations for preventable chronic conditions and shorter longevity [19,21,22]. While Hawai'i's official poverty rate is very low, when cost-ofliving is factored in, in 2017 Hawai'i had the 10th highest poverty rate of all states, [23] and rural populations and lower income communities in the state have similar poor outcomes [19,24].…”
Section: Hawai'i Contextmentioning
confidence: 99%
“…They make up two of the five major racial/ethnic groups in Hawai'i, the study location, comprising an estimated 38.5% (21.3% Native Hawaiian and 17.2% Filipino) of the state's total population [45]. Compared to the other major racial/ethnic groups in Hawai'i, Native Hawaiians and Filipinos often have poorer health outcomes, including high rates of chronic conditions and maternal and child health inequities, as well as significant socioeconomic challenges and limited access to high quality, culturally relevant health care [46][47][48][49][50]. The consequences of these inequities include an over 10-year gap in life expectancy between Native Hawaiians and Chinese, the longest lived racial/ethnic group in the state, and a 6-year gap between Filipinos and Chinese [45].…”
Section: Study Focusmentioning
confidence: 99%
“…40 The provision of culturally competent patient care despite differences is ripe for intervention, as multiple other studies have also identified the critical intersection with patient outcomes, perceived trust, and mutual respect. 28,41,42 Time constraints perplex and trouble both patients and providers. Both parties agree that more time during a visit enables a greater understanding of patients' life circumstances, while the current time constraints seemingly threaten patientphysician relationships.…”
Section: Iscussionmentioning
confidence: 99%